Design of Non-Circular Pulleys for Torque Generation: A Convex Optimisation Approach - Ludovico, Daniele; Guardiani, Paolo; Lasagni, Francesco; Lee, Jinoh; Cannella, Ferdinando; Caldwell, Darwin G. (IEEE robotics and automation letters, 2021)
Nowadays, robotic research focuses more and more on attaining energy-efficient and safe solutions. They are key-aspects of industrial robots, such as inspection and maintenance robots. The introduction of a mechanism that passively compensates the joint torque caused by the weight of the robot may offer a valid solution. Avoiding the need for actuators to balance gravity torques helps decrease the power consumption and the size of the actuators. Furthermore, a passive gravity compensation mechanism allows the robot to hold a static position without the need for an external power source, hence avoiding the risk of collapsing in case of failure of the actuators. This work focuses on designing a torque generator composed of a non-circular pulley and a spring, which, by solving a convex optimisation problem, offers a new methodology for creating any generic torque and thereby also succeeds in solving gravity compensation problems. This methodology guarantees the outcome of feasible non-circular pulleys which minimise the torque required to perform any specific task.